2001
DOI: 10.1254/jjp.85.365
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitors and AT1-Receptor Antagonist Restore Nitric Oxide Synthase (NOS) Activity and Neuronal NOS Expression in the Adrenal Glands of Spontaneously Hypertensive Rats

Abstract: ABSTRACT-During development of hypertension in spontaneously hypertensive (SHR) rats, the activity of adrenal nitric oxide synthase (NOS) was investigated. SHR and Wistar-Kyoto (WKY) rats were studied at different ages: 3 -4, 7 -8 and 12 -13 weeks after birth. Basal NOS activity was measured by the ability of homogenate to convertAt all ages, SHR rats exhibited 50 -60% reduction in NOS activity when compared to age-matched WKY rats. In a following study, SHR rats (12 -13 weeks) were treated chronically with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Similar findings were also obtained about the mechanisms underlying the hypotensive action of losartan in rats of the phenol-injury model [108]. The basal NOS activity and protein expression of nNOS were increased in adrenal glands of SHR chronically treated with losartan, captopril, or enalapril when compared with control rats; eNOS and iNOS were undetectable, suggesting that the upregulation of nNOS protein in adrenals may be one of the mechanisms of action of these antihypertensives [109].…”
Section: Antihypertensive Therapy In Relation To Neuronal Nitric Oxidsupporting
confidence: 77%
“…Similar findings were also obtained about the mechanisms underlying the hypotensive action of losartan in rats of the phenol-injury model [108]. The basal NOS activity and protein expression of nNOS were increased in adrenal glands of SHR chronically treated with losartan, captopril, or enalapril when compared with control rats; eNOS and iNOS were undetectable, suggesting that the upregulation of nNOS protein in adrenals may be one of the mechanisms of action of these antihypertensives [109].…”
Section: Antihypertensive Therapy In Relation To Neuronal Nitric Oxidsupporting
confidence: 77%
“…However, we could not rule out the effect of captopril on NO in other tissues. It has been reported that administration of captopril to SHR did not affect the protein expression of NOS-2 and NOS-3 but upregulated NOS-1 in the adrenal glands (Qadri et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the immunohistochemical study showed that the density of nNOS-immunopositive nerve fibers was markedly reduced in the mesenteric arteries of 2K1C-RHRs, supporting the present findings that neuronal NO modulation in adrenergic neurotransmission is decreased in 2K1C-RHRs. It has been reported that nNOS expression is decreased in the adrenal glands of SHR 31 and that soluble guanylate cyclase, the key precursor of NO cyclic guanosine monophosphate-dependent effects, is downregulated in the aorta 32 and atria 33 of SHRs. The reninangiotensin system is strongly augmented in 2K1C-RHRs.…”
Section: Discussionmentioning
confidence: 99%
“…The active substance of renin-angiotensin system, angiotensin II, is a potent vasoconstrictor, having strong effects on vascular tone regulation, facilitating sympathetic neurotransmission 34 and reducing the bioavailability of NO as a result of increasing oxidative stress. 28,3,31 Furthermore, it has been reported that high blood pressure causes increased oxidative stress in the vasculature. 35 Therefore, it is very likely that the acute increase in renin-angiotensin system and high blood pressure in 2K1C-RHRs blunts the inhibitory modulation of NO-containing nerves in adrenergic neurotransmission and thereby leads to further facilitation of adrenergic neurotransmission.…”
Section: Discussionmentioning
confidence: 99%